Distance determination method of dust particles using Rosetta OSIRIS NAC and WAC data. (1st September 2017) - Drolshagen, E.; Ott, T.; Koschny, D.; Güttler, C.; Tubiana, C.; Agarwal, J.; Sierks, H.; Barbieri, C.; Lamy, P.I.; Rodrigo, R.; Rickman, H.; A'Hearn, M.F.; et al.
Abstract: The ESA Rosetta spacecraft has been tracking its target, the Jupiter-family comet 67P/Churyumov-Gerasimenko, in close vicinity for over two years. It hosts the OSIRIS instruments: the Optical, Spectroscopic, and Infrared Remote Imaging System composed of two cameras, see e.g.Keller et al. (2007) . In some imaging sequences dedicated to observe dust particles in the comet's coma, the two cameras took images at the same time. The aim of this work is to use these simultaneous double camera observations to calculate the dust particles' distance to the spacecraft. As the two cameras are mounted on the spacecraft with an offset of 70 cm, the distance of particles observed by both cameras can be determined by a shift of the particles' apparent trails on the images. This paper presents first results of the ongoing work, introducing the distance determination method for the OSIRIS instrument and the analysis of an example particle. We note that this method works for particles in the range of about 500–6000 m from the spacecraft.